2023
DOI: 10.3389/fmicb.2023.1091755
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sterilization and chemical fertilizer on the microbiota of oil palm seedlings

Abstract: Soil nutrients and microbiota are known as essential components for healthy plant growth and crop productivity. However, limited studies have been conducted on the importance of soil microbiota in the early growth of oil palm seedlings (Elaeis guineensis Jacq.) under the influence of nitrogen, phosphorus and potassium (NPK) compound fertilizer (nitrogen, phosphorus, and potassium). In this study, we analyzed the root microbial community associated with seedlings grown under normal and sterilized soil condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As illustrated in Figure S1B, each infusion was divided into two equal volumes, on the one hand, the MB infusion contained microorganisms and nutrients from the soil, and on the other hand, the E infusion was sterilized in an autoclave for 30 min at 121°C (15 psi). In this regard, previous works have shown that the sterilization process does not change the overall macronutrient availability (Ding et al, 2023), and thus the E infusions only contained nutrients from the soil after being sterilized (Autester ST, P. Selecta, Spain autoclave). To ensure that the E infusions did not contain bacteria, 1 mL of each E infusion was plated ('Plate Count Agar (PCA)', 2011) and incubated at 28°C for 7 days to check bacteria growth.…”
Section: Preparation Of Soil Infusions For Inoculationmentioning
confidence: 98%
“…As illustrated in Figure S1B, each infusion was divided into two equal volumes, on the one hand, the MB infusion contained microorganisms and nutrients from the soil, and on the other hand, the E infusion was sterilized in an autoclave for 30 min at 121°C (15 psi). In this regard, previous works have shown that the sterilization process does not change the overall macronutrient availability (Ding et al, 2023), and thus the E infusions only contained nutrients from the soil after being sterilized (Autester ST, P. Selecta, Spain autoclave). To ensure that the E infusions did not contain bacteria, 1 mL of each E infusion was plated ('Plate Count Agar (PCA)', 2011) and incubated at 28°C for 7 days to check bacteria growth.…”
Section: Preparation Of Soil Infusions For Inoculationmentioning
confidence: 98%